AN ANALYSIS OF THE PATTERN AND THE RISK FACTORS OF ADVERSE DRUG REACTIONS AT A TERTIARY CARE HOSPITAL - BABY, MINU; RG, ANAND; MATHEW, ANU ELINE; SHAJAHAN, JIHANA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to analyze the pattern and risk factors of adverse drug reactions (ADR) in a tertiary care hospital. Methods: In this retrospective study, all the suspected ADRs reported to ADR monitoring center were analyzed for the demographic details, its temporal association, status of recovery, seriousness and outcome of reaction, details of the suspected and concomitant medications. Data on various predisposing factors responsible for an ADR, such as presence of co-morbidities, use of Fixed Dose Combinations (FDC), improper monitoring, presence of drug interactions, and presence of polypharmacy were also collected. Descriptive statistics and Chi-square were used for data analysis. A p value of <0.05 was taken as level of significance. Results: Out of the total 233ADRs, 48.9% were reported among geriatric patients. The study showed a female preponderance with 51.9%. The highest number of ADRs was reported from the therapeutic class of antimicrobials 18.9%. The skin and appendages constituted the most common organ system affected with 33.5%. Out of 106 serious ADRs, majority required prolonged hospitalization 62.3%. About 78.1 % of reactions were found to be predictable and 72.5% preventable. A positive association was found between ADR and co-exiting co-morbidity (60%), polypharmacy (66.5%), and use of FDC (18.45%). ADRs secondary to inadequate monitoring was 7.7% and those due to drug-drug interaction was 6.5%. Conclusion: Female population, age >60 years, and presence of concomitant co-morbidities were the patient related risk factors and polypharmacy, drug-drug interactions, and inadequate monitoring were the drug related risk factors for development of ADRs.